Antimicrobial peptides expression by ocular surface cells in response to Acanthamoeba castellanii: an in vitro study. Issue 11 (1st August 2010) - Otri, A M; Mohammed, I; Abedin, A; Cao, Z; Hopkinson, A; Panjwani, N; Dua, H S
Abstract : Aims: Antimicrobial peptides (AMPs) are natural effectors of the innate immune response. Much work has been done to study their response and effects on bacterial and viral infection. Little if any information is available in relation to protozoal infections. The aim of the study was to comprehensively study the gene expression of the ocular AMPs in human corneal limbal epithelial cells stimulated with Acanthamoeba castellanii (AC). Methods: Human corneal limbal epithelial cells were exposed to AC at different time points, up to 9 h, the genomic profile of the AMPs were analysed at these time point using real time PCR. corneal limbal epithelial cells not infected with AC were used as controls. Results: Seven of the eight studied AMPs showed statistically significant upregulation in gene expression. Human beta Defensin 3 (hBD3) showed a very significant 10-fold upregulation in the exposed cells and Ribonuclease-7 (RNase-7) showed a very early and consistent increase. Human beta Defensin 1 (hBD1) was the only downregulated AMP. Conclusions: The study data suggests a possible role of the AMPs in combating the amoebic infection at the ocular surface. Using AMPs singly or in combination is a promising avenue for further exploration in the treatment of the sight threatening Acanthamoeba keratitis.